Optimization of Xanthan Gum Production from Grape Juice Concentrate Using Plackett-Burman Design and Response Surface Methodology - Tahereh Ghashghaei; Mohammad Reza Soudi; Saman Hoseinkhani (Applied Food Biotechnology, 2016)
Low grade grape juice concentrate was used as carbon source for xanthan production. Significant factors affecting xanthan concentration, productivity and viscosity were investigated using Plackett-Burman Design. Based on the obtained results, carbon and nitrogen concentrations, inoculum size and agitation rate, were assumed as significant factors. Broth culture viscosity and xanthan concentration were optimized using Response Surface Methodology with four independent variables: carbon source (30, 40, 50 g l-1), ammonium sulfate as nitrogen source (0.5, 1.25, 2 g l-1), agitation (150, 200, 250 rpm) and inoculum size (5, 10, 15% v v-1). Optimum level for each factor was obtained by desirability function approach. The average of xanthan gum production and its viscosity under optimized conditions were recorded as 14.35 g l-1 and 1268 cP, respectively. The average yield of production and productivity of xanthan within 72 h under optimized conditions were 35% and 0.19 g l-1 h-1, respectively. The current study showed the potential of low-grade grape juice concentrate as an economic carbon source for xanthan gum production.